Gene-gene interaction and association of Wnt/Β-catenin signalling pathway gene polymorphisms with ankylosing spondylitis susceptibility in the Chinese Han population - Rui Liu; Xu Zhang; Guangming Jiang; Yubo Ma; Jiajia Yang; Meng Wu; Renfang Han; Mengya Chen; Yaping Yuan; Xingxing Hu; Meijuan Pan; Shengqian Xu; et al. (Taylor & Francis Group, 2019)
Objectives: To explore the genetic interaction between Wnt/β-catenin signalling pathway genes and ankylosing spondylitis (AS) in the Chinese population. Methods: Six single-nucleotide polymorphisms (SNPs) in DKK1, LRP5, LRP6, and SOST genes were genotyped in 673 AS patients and 687 healthy controls by using SNPs can Technic. Single marker genetic association analysis was performed. Haplotypes were constructed after linkage disequilibrium analysis; additive, multiplicative, and higher-order interactions were analysed. Results: The DKK1 gene rs1569198 polymorphism was significantly associated with AS susceptibility in females (χ2 = 4.55, p = .03), but the association disappeared after Bonferroni correction. Moreover, a haplotype (T-G) in the DKK1 gene showed a protective role in AS susceptibility in females (p = .04). Significant additive interactions were observed between DKK1: rs1896368 and LRP5: rs3736228, relative excess risk due to interaction (RERI) = 0.40, 95% CI = 0.08 - 0.71; attributable proportion due to interaction (AP) = 51%, 95% CI = 0.07 - 0.94, DKK1: rs1569198 and LRP5: rs3736228 (RERI = 0.49, 95% CI = 0.12 - 0.86; AP = 49%, 95% CI = 0.17 - 0.82), LRP5: rs3736228 and SOST: rs4792909 (RERI = 0.33, 95% CI = 0.002 - 0.65; AP = 41%, 95% CI = 0.01 - 0.81) in the dominant model. Conclusions: Our research implies a potential gene-gene interaction, thus revealing the importance of the Wnt/β-catenin signalling pathway for understanding the genetic architecture of AS.